Implikasi Kesulitan Keuangan dan Variabel Makroekonomi terhadap Return Saham dengan Variabel Moderasi Arus Kas Operasi - Ikhlasillah, Muhammad; Wiratno, Adi; Rachbini, Widarto (SEKOLAH PASCASARJANA PRESS, 2018)
This study aims to examine the implications of the financial distress, interest rate and exchange rate to stock returns on textile and garment companies in Indonesia, which listed on the Indonesia Stock Exchange for the period 2012-2015. The operating cash flow is used as a moderating variable to examine the correlation between financial distress and stock returns. There are 15 companies that are used as samples for the study were selected based on purposive sampling method. Meanwhile, fixed effect model of the data panel linear regression method selected for data analysis. The quantitative data was taken from ICMD and Capital Market Reference Center Indonesia Stock Exchange. By using significance level of 5%, study results showed financial distress as Altman Z-score influence positively but insignificant on stock returns and depreciation of exchange rate influence positively and significant on stock returns. Meanwhile, increasing interest rate impact on stock returns negatively but not significant. The study also summarize that operating cash flow cannot moderate the correlation between financial distress and stock returns and this variable classified as predictor moderator. The study results also showed financial distress, interest rates and exchange rates had significant impact on stock returns simultaneously.